Optimization of Financial Literacy Among Micro, Small, and Medium Enterprises Through Simple Financial Management Practices - Fajar Pasaribu; Widia Astuty; Muhammad Hasan Pasaribu; Miss Diana Laewang (Forum Kerjasama Pendidikan Tinggi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are sectors that have a strategic role in supporting national economic growth, including in Belitung Regency. However, one of the fundamental problems faced by most MSME actors is the low financial literacy and business financial management skills. This condition has an impact on the inability of business actors to manage cash flow, separate personal and business finances, and carry out long-term financial planning effectively. This community service activity aims to improve financial literacy and simple financial management skills for MSME actors in Belitung Regency so that they can manage their businesses in a more professional and competitive manner. The implementation method includes training, mentoring, and direct practice regarding recording financial transactions, preparing simple financial statements, and planning business budgets. This activity was carried out by involving MSME actors from various economic sectors in Belitung Regency. The results of the activity showed an increase in participants' understanding of the importance of financial recording, simple report preparation, and financial management separate from personal finance. Participants also showed high enthusiasm in applying the simple financial planning and recording format provided. Overall, this activity has succeeded in making a real contribution in increasing the capacity and independence of MSME actors in managing business finances. With the increase in financial literacy, it is hoped that MSMEs in Belitung Regency can grow stronger, adaptive, and competitive to face regional and national economic challenges.